2016
DOI: 10.1177/1524839916676463
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy and Public Policy Perceptions and Involvement of Master Certified Health Education Specialists

Abstract: Master Certified Health Education Specialists (MCHES; n = 186) participated in a mail survey on advocacy and public policy. Over half of participants reported that they had contacted a public official or provided policy-related information to consumers or other professionals. Participants identified barriers and benefits to influencing public policy. The greatest benefit was identified as improving the health or welfare of the public while the greatest barrier was that they were busy with other priorities. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
7
1
Order By: Relevance
“…The regression analysis in this study showed that students with greater perceived advocacy/policy-related knowledge, self-efficacy, number of trainings, and perceived benefits participate in more advocacy/policy activities. Our findings are comparable to those of Kerr and colleagues (2017), who found that number of training sources, self-efficacy, perceived benefits, knowledge, perceived barriers, and age were predictors of advocacy/public policy activities among MCHES professionals. Frequent opportunities to engage in advocacy or advocacy/public policy-related skill development can result in mastery experiences that build self-efficacy and engagement (Bandura, 1977; Bliss & Dressner, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The regression analysis in this study showed that students with greater perceived advocacy/policy-related knowledge, self-efficacy, number of trainings, and perceived benefits participate in more advocacy/policy activities. Our findings are comparable to those of Kerr and colleagues (2017), who found that number of training sources, self-efficacy, perceived benefits, knowledge, perceived barriers, and age were predictors of advocacy/public policy activities among MCHES professionals. Frequent opportunities to engage in advocacy or advocacy/public policy-related skill development can result in mastery experiences that build self-efficacy and engagement (Bandura, 1977; Bliss & Dressner, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Prior studies of primarily health education professionals indicated that respondents engaged in basic advocacy participation such as voting, while fewer engaged in more influential, higher level activities that require more time and effort (Holtrop, Price, & Boardley, 2000; Kerr et al, 2017; Mahas, Van Wasshenova, Everhart, Thompson, & Boardley, 2016). One of the most commonly cited barriers to participation found in multiple studies is being busy with other priorities (Holtrop et al, 2000; Kerr et al, 2017; Mahas et al, 2016; Thompson, Boardley, Kerr, Greene, & Jenkins, 2009), along with a general lack of training or specific training received through college coursework (Holtrop et al, 2000; Kerr et al, 2017; Mahas et al, 2016; Radius, Galer-Unti, & Tappe, 2009). Studies assessing advocacy and policy involvement of college students indicated a lack of participation, knowledge, self-efficacy, and training (Cooper, 1986; Cox et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few public health practitioners are comfortable with policy concepts, especially in the public sphere (Hernandez, Rosenstock, & Gebbie, 2003). They report limited engagement with (Kerr et al, 2017) and sometimes an aversion to public policy (McFarlane & Gordon, 1992). Perceived barriers to public health policy engagement include scarce resources and also a lack of familiarity with policy, limited confidence in advocacy skills, and frustration with policy processes (Mahas, Van Wasshenova, Everhart, Thompson, & Boardley, 2016; Moreland-Russell, Zwald, & Golden, 2016).…”
mentioning
confidence: 99%
“…Therefore, the purpose of this paper is to present a particular case of nursing advocacy around voting rights to explore both the challenges inherent in this competency and to provide practical suggestions to support nurses who seek to enact public policy advocacy for social justice. Providing recommendations to overcome the challenges of public policy advocacy can begin to fill the gaps in health professional education (Kerr, et al, 2017).…”
mentioning
confidence: 99%